Gastrointestinal parasites of the Polish primitive horses from the Biebrza National Park - Slivinska K.; Wróblewski Z.; Gawor J. (Helminthologia, 2016)
Thirty-one Polish primitive horses (Equus caballus) from three herds (two from the reserve and onefrom the stable) were dewormed with ivermectin+praziquantel and examined for the gastrointestinalparasite fauna. A total of 21.231 parasites were collected from the faeces at 24, 36 and 48 hoursposttreatment. There were 35 nematode species, one cestode and one botfl y larva. Strongyloideswesteri infection was confirmed pretreatment by faecal sample examination and no threadwormspecimens were found after deworming. Large and small strongyle prevalence was 90 % – 100 % and represented by 31 species. Among a total of 25 cyathostome species recovered (from 19 to 24in each group), five species (C. catinatum, C. minutus, C. longibursatus, C. nassatus and C. ashworthi)had a prevalence of 100 % in three groups of horses. Meanwhile 14 species were 100 % prevalent in one herd. A total of six large strongyle species were found in adult horses. Oxyuris equiwas recorded in 60 – 100 % of the horses while Parascaris equorum was detected in 100 % of foalsand 16.7 % – 30 % of adult mares. Habronema muscae was found in 30 % of the horses from onefree-ranging herd. Tapeworms (Anoplocephala perfoliata) were found in 90 % of the horses from onefree-ranging group, whereas botfl y larvae (Gasterophilus intestinalis) were found in 50 – 80 % of allsurveyed horses. The present results are compared with earlier studies of Polish primitive wild horsesfrom similar reserves in Poland. A total of 36 gastrointestinal parasite species were recorded fromwild and stabled horses from the Biebrza National Park. This is in comparison with 35 such speciesin free-ranging and stabled horses from the Roztocze National Park and with 28 such species offree-ranginghorses from the Popielno forest reserve.